Behavioral Study of Parkinson's Disease Rats Model with DigiGaitTM Imaging System - LIU Xinhao; MA Shujie; DING Daofang; LUO Kailiang; MA Xinran; JIANG Wenling; HU Jun (康复学报)
ObjectiveTo detect the feasibility of DigiGaitTM Imaging System in evaluating gait changes in rats model with Parkinson's disease (PD).MethodsA total of 24 clean male SD rats were randomly divided into normal group, sham operation group and model group, with eight rats in each group. In the model group, 6-Hydroxydopamine (6-OHDA) was injected into the brain with unilateral 2-point method to establish PD rats model. The sham operation group was injected with 0.2% ascorbic acid solution with the same method, and the normal group did not receive any surgical treatment. After successful preparation of the model, DigiGaitTM Imaging System was used to analyze temporal subcomponent (swing duration, braking duration, stance duration, stance factor), spatial subcomponent (stride frequency, stride length, stance width, gait symmetry, paw overlap distance, paw placement positioning) and postural subcomponent (paw angle, step angle, paw area).Results1) Temporal subcomponent: compared with the normal group, the swing duration, braking duration and stance duration of left front paw, left hind paw and right front paw in the model group were significantly prolonged (P<0.05), and the braking duration and swing duration of right hind paw in the model group were significantly prolonged (P<0.05). Compared with the sham operation group, the swing duration, braking duration and stance duration of left front paw, left hind paw and right front paw in the model group were significantly prolonged (P<0.05), and the braking duration of right hind paw in the model group was significantly prolonged (P<0.05). 2) Spatial subcomponent: compared with the normal group and the sham operation group, the front and hind limb stance width of the model group significantly increased (P<0.05), step frequency of four paws, stride length of left paws and paw placement positioning and gait symmetry in the model group significantly decreased (P<0.05). But stride length of right paws and overlap distance of left and right paws in the model group had no significant changes (P>0.05). 3) Postural subcomponent: compared with the normal group and the sham operation group, the contact area of left front paw, left hind paw and right hind paw with running belt in the model group significantly decreased (P<0.05), there was no significant difference in paw area, paw angle and gait angle between the right front paw and the running belt (P>0.05).ConclusionDigiGaitTM Imaging System can objectively evaluate walking, balance and coordination functions of PD rats, which has the potential to be widely applied in PD related basic research.